A game of persuasion: influencing persuasive game appraisals through presentation frames and recommendation sources - Groen, Marloes A.; Jacobs, Ruud S. (Frontiers in Psychology, 2023)
Introduction As games made with the explicit or implicit purpose of influencing players’ attitudes, persuasive games afford a new way for individuals to reflect and elaborate on real-world issues or topics. While research points to effects of these games on their players, little is known about their practical impact. The current study focuses on the decision-making process that takes place between first hearing about a game and deciding to play it. Three elements in a game’s presentation to potential players were explored: (1) the way it is framed as an entertaining experience, (2) the way it is framed as intending to persuade its players, and (3) whether it comes recommended by automated systems or through electronic word-of-mouth. These factors were chosen in line with theoretical arguments around framing, eudaimonia, and source credibility. Methods A two (entertainment frame: hedonic versus eudaimonic) by two (persuasive intent frame: obfuscated versus explicit) by two (source of recommendation: system- versus peer-based) between-subjects experimental design was performed across (N = 310) randomly distributed participants. Measures were adapted from previous research and included selection and play behavior, attitudes, and obtrusiveness of persuasive intent, among others. Results and Discussion Results show that frames need to be congruent to be effective, with the most effective stimuli being those where persuasive intent was clear and players could expect to engage meaningfully. Peer recommendations led to greater play intention than system-based varieties. While intention to play positively related to actual play behavior, this relationship was likely the result of avid game players displaying more interest in the game regardless of the study’s manipulations. Implications are drawn from the advantages of being open about persuasive intent and the composition and drivers of a persuasive game’s target audience.